Bitemporal epilepsy: A specific anatomo-electro-clinical phenotype in the temporal lobe epilepsy spectrum. (September 2015) - Didato, Giuseppe; Chiesa, Valentina; Villani, Flavio; Pelliccia, Veronica; Deleo, Francesco; Gozzo, Francesca; Canevini, Maria Paola; Mai, Roberto; Spreafico, Roberto; Cossu, Massimo; Tassi, Laura
Highlights: Bitemporal epilepsy (BTLE) significantly differs from unitemporal epilepsy (UTLE). BTLE patients had an older age at epilepsy onset and rare positive brain MRI. Interictal/ictal EEG activity and dystonia were more frequently bilateral in BTLE. Head deviation and oroalimentary automatisms were less frequent in BTLE. The identified pattern allows the non-invasive recognition of BTLE. Abstract: Purpose: Temporal lobe epilepsy (TLE) with bilateral ictal involvement (bitemporal epilepsy, BTLE) is an intriguing form of TLE whose characteristics need to be carefully identified as BTLE patients are not good surgical candidates. The purpose of this study was to define the anatomo-electro-clinical features differentiating BTLE from unilateral TLE (UTLE). Methods: Forty-eight BTLE patients underwent long-term video-EEG monitoring (VEEG) and experienced seizures with bilateral temporal lobe involvement. Their main electro-clinical (demographics, interictal and ictal EEG, ictal signs) and neuro-imaging [brain magnetic resonance imaging (MRI)] data were compared with those of a group of 38 UTLE patients. Results: In comparison with the UTLE patients, the BTLE cohort was significantly older at the time of epilepsy onset ( p  = 0.023), more frequently experienced bilateral asynchronous interictal epileptiform discharges during wakefulness ( p  = 0.001) and sleep ( p  < 0.001), bilateral upper limb dystonia ( p  = 0.005), and auditory auras ( p  = 0.027), and less frequently showed a recognisable initial ictal EEG pattern of focal flattening or low-voltage fast activity ( p  < 0.001), post-ictal memory of seizures ( p  = 0.001), staring ( p  < 0.001), head deviation ( p  = 0.004), oro-alimentary automatisms ( p  = 0.006), and positive brain MRI ( p  < 0.001). MRI revealed neoplastic lesions ( p  = 0.007) or alterations other than hippocampal sclerosis ( p  = 0.028) only in the UTLE patients. Conclusion: The possibility of recognising BTLE patients during pre-surgical evaluation or being able to suspect bitemporal seizures before VEEG by identifying particular anatomo-electro-clinical patterns is diagnostically important for epileptologists and can help to prevent possible surgical failures.